2022
DOI: 10.1155/2022/2195330
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-To-Lymphocyte and Neutrophil-To-Lymphocyte Ratios Predict Intestinal Injury in Male Heroin Addicts

Abstract: Objective. To explore the potential link between gut damage and proinflammatory cytokines in heroin-dependent patients. Methods. We retrospectively analyzed and compared partial blood counts and biomarkers of intestinal injury and their potential correlations in 38 male heroin abuse patients and 29 healthy male participants. In addition, we compared and assessed proinflammatory cytokines and immune cells in 10 heroin abuse patients and 10 healthy participants. Results. Neutrophil counts, platelets/lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%